An occupational therapy intervention for residents with stroke living in care homes in the United Kingdom: A content analysis of occupational therapy records from the OTCH trial. (July 2015) - Sands, Gina; Kelly, Debbie; Fletcher-Smith, Joanna; Birt, Linda; Sackley, Catherine
Introduction: This study aimed to describe the content of occupational therapy delivered in a randomized controlled trial of United Kingdom care home residents with stroke (The Occupational Therapy in Care Homes (OTCH) trial). The trial intervention aimed to maintain or improve residents' activity levels in relation to personal activities of daily living and mobility. Method: A qualitative design was adopted using content analysis to thematically code and analyse the occupational therapy notes of residents in the intervention arm of the trial. Treatment notes comprised of an initial assessment, a goal and treatment plan and a description of activities at each visit. A purposive sample of 50 sets of therapy notes was selected reflecting the geographical locations, care home types and resident characteristics observed in the OTCH trial intervention group. Findings: Occupational therapists individually assessed residents' function and goals. Planning was sometimes client-centred, but not all residents were able to share personal goals. Carers impacted on the success of the intervention. Treatment outcomes in relation to increasing functional activity were noted in some cases, but not always fully realized in this frail population. Conclusion: Increasing functional activity is challenging in care home populations; future studies should assess occupational therapy for residents in relation to leisure or social activities.